Development of Virtual Laboratory Media for Virus Materials to Improve Students' Higher Order Thinking Skills in Senior High School - Asri, Widi; Isnaeni, Wiwi; Susanti, R. (Universitas Negeri Semarang, 2023)
This study aims to (1) describe the validity of under-development virtual laboratory media of virus material, (2) describe practicality of under-development virtual laboratory media of virus material, (3) describe effectiveness of under-development virtual laboratory media of virus material.This study is research and development using the ADDIE model (analyze, design, develop, implement, and evaluate). The study instruments are compiled including virtual laboratory media validation sheets for experts, virtual laboratory media practicality sheets for biology teachers and student, critical thinking questions and procedural skills. The application of virtual laboratory media includes limited trials and field trials. The field trial subjects are students of class X at State Senior High School 1 Wonosobo. The field trial design for this research is a pretest-posttest control group design. The practicality of virtual laboratory media is analyzed from data on filling out the eligibility sheet by media and material experts by managing the average score and categorizing the data into ideal ratings. The practicality of virtual laboratory media is analyzed from the data of filling in the practicality sheet by the biology teacher by managing the average score by categorizing the data as an ideal assessment. The effectiveness of virtual laboratory media is analyzed from n-gain data on critical thinking and procedural skills using the Mann-Whitney U test.The results showed that (1) the under-development virtual laboratory media is valid for use in teaching biology on viruses based on expert validation (2) the under-development virtual laboratory media is practically used in learning biology material on viruses based on the biology teacher's assessment. Thus, it becomes a solution for laboratory tools and materials for State Senior High School 1 Wonosobo which can facilitate their students in improving HOTS skill (3) the under-development virtual laboratory media effectively improves students' higher-order thinking skills based on Mann Withey U analysis on trial data.